흡수 조건 및 부식 생성물에 의한 MEA 수용액의 변성 특성 - 남성찬(Sung Chan Nam); 송윤아(Yoon Ah Song); 백일현(Il Hyun Baek); 윤여일(Yeo Il Yoon); 유정균(Jeong Kyun You); 이창하(Chang Ha Lee) (한국수소 및 신에너지학회 논문집, 2016)
The absorbent loss due to degradation in $CO_2$ capture process using aqueous alkanol amine solution has adverse effect on the economics of overall process. The degradation causes absorbent loss, equipment corrosion, foaming, adhesive material producing and viscosity increase in operation. In this study, the degradation characteristics of $CO_2$ capture process using MEA (monoehtanolamine) under various conditions such as $O_2$ partial pressure, $CO_2$ loading and absorbent temperature. The effects of iron, which generated from the equipment corrosion, on absorbent degradation were studied using $Fe_2SO_4$ containing MEA solution. The produced gases were analyzed by FT-IR(Fourier Transform Infrared Spectrophotometer) and the specifically measured $NH_3$ concentration was used as a degradation degree of aqueous MEA solution. The experiments showed that the higher $CO_2$ loadings (${α}$), $O_2$ fraction ($y_{O2}$) and reaction temperature enhanced the more degradation of aqueous MEA solution. Comparing other operation parameters, the reaction temperature most affected on the degradation. Therefore, it could be concluded that the above parameters affects on degradation should be considered for the selections of $CO_2$ absorbent and operating conditions.